Primordial rare gases in Belgica-7904 (C2) carbonaceous chondrite - Nagao,Keisuke; Inoue,Kensaku; Ogata,Koreichi (1984)
P(論文) Belgica-7904 (C2) carbonaceous chondrite was analyzed for rare gas isotopic compositions with stepwise heating extraction method. Primordial rare gases are dominant, whereas the concentrations of radiogenic ^4(He) and ^<40>(Ar) are lower than those to be expected from radioactive decay. Cosmic-ray exposure age of 0.7 my was obtained with cosmogenic ^<21>(Ne). Ne-E component was found in a 900-1100℃ range and its concentration was 1.2×(10)^<-9>(cm)^3 STP/g. Excessive heavy Xe isotopes in a 900℃ fraction have CCF-Xe spectrum. ^<20>(Ne), ^<84>(Kr) and ^<132>(Xe) in the highest temperature fraction of 1800℃ are enriched. The enrichments may be due to a stellar nucleosynthesis or due to a neutron irradiation of high temperature condensates. departmental bulletin paper